Efficiency wage theory : an analysis into Singapore manufacturing sector - Chua, Sin-Chet (2014)
This paper attempts to examine and provide econometric evidence in support of the efficiency wage theory for manufacturing sector in Singapore. Evidence in support of efficiency wage is found for 3 out of 18 industries within the manufacturing sector in Singapore based on both OLS and GMM regression results. One possible way to account for efficiency wage is that higher wages could have reduced shirking which boosts workers’ productivity. In Singapore, Wage Credit Scheme and Progressive Wage Model are two recent policies that seem to resemble the mechanics of an efficiency wage framework.